2019
DOI: 10.1111/cmi.13021
|View full text |Cite
|
Sign up to set email alerts
|

Histamine releasing factor and elongation factor 1 alpha secreted via malaria parasites extracellular vesicles promote immune evasion by inhibiting specific T cell responses

Abstract: Protozoan pathogens secrete nanosized particles called extracellular vesicles (EVs) to facilitate their survival and chronic infection. Here, we show the inhibition by Plasmodium berghei NK65 blood stage‐derived EVs of the proliferative response of CD4+ T cells in response to antigen presentation. Importantly, these results were confirmed in vivo by the capacity of EVs to diminish the ovalbumin‐specific delayed type hypersensitivity response. We identified two proteins associated with EVs, the histamine releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Recent studies showed that intracellular parasites utilize exosome mediated signaling with the host immune cells to alter host immunity (2527) Further, in the early time points after infection, we observed that miR-21 levels were altered in bystander cells (RFP/mCherry negative population) in addition to the parasitized cells (RFP/mCherry positive population, Figures 2B–D). Consistent with this observation, at 12 h post infection, IL-12 levels were also significantly higher in LdCen −/−mCherry parasitized cells compared to LdWT RFP infection.…”
Section: Resultsmentioning
confidence: 52%
“…Recent studies showed that intracellular parasites utilize exosome mediated signaling with the host immune cells to alter host immunity (2527) Further, in the early time points after infection, we observed that miR-21 levels were altered in bystander cells (RFP/mCherry negative population) in addition to the parasitized cells (RFP/mCherry positive population, Figures 2B–D). Consistent with this observation, at 12 h post infection, IL-12 levels were also significantly higher in LdCen −/−mCherry parasitized cells compared to LdWT RFP infection.…”
Section: Resultsmentioning
confidence: 52%
“…EF1a is also found in extracellular vehicles (EVs) of Plasmodium berghei. EF1a in combination with another EVs factor, termed histamine releasing factor (HRF), inhibits antigen-specific T cell responses through interference with key phosphorylation pathways associated with T cell receptor (TCR) signaling [12]. This action facilitates parasite escape from host immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…There are an interesting fact that the 12 amino acid deletions in EF1a have been found in some pathogenic protozoans of major global health importance, including Leishmania donovani [10,11], Plasmodia spp. [12], Giardia lamblia [13], Toxoplasma gondii [14], Cryptosporidium parvum [15,16], Trypanosoma cruzi [17], T. brucei brucei, and Entamoeba histolytica [10,18]. The same amino acid sequence deletion compared with human EF1a, indicated targeting the exposed region of EF1a common to all of these pathogens could have far-reaching benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-liquid chromatography and MS analyses were performed on a 2 h run per replicate as previously described [ 46 ]. The mass spectrometry experimental data were compared with theoretical data using Mascot v2.5.1 (Matrix science) on a Homo sapiens (23,076 sequences) SwissProt protein database (October 2018) and an in-house database containing the E571K sequence variant of XPO1.…”
Section: Methodsmentioning
confidence: 99%